Rapid detection of potato late blight using a loop-mediated isothermal amplification assay - Liang KONG; Hui-bin WANG; Shuai-shuai WANG; Ping-ping XU; Ruo-fang ZHANG; Suomeng DONG; Xiao-bo ZHENG (Journal of Integrative Agriculture)
Potato late blight caused by Phytophthora infestans is one of the most destructive plant diseases that threaten global food security. Early and effective diagnosis of P. infestans is required before disease management decisions are made. Here, we developed a quick protocol to detect P. infestans based on a loop-mediated isothermal amplification (LAMP) assay. The P. infestans specific multiple copy DNA sequences (PiSMC), a transposon-like element, provides an ideal target for molecular detection of this pathogen. We designed highly specific and sensitive primers allowing effective LAMP detection of the pathogen at 64°C in 70 min. In the validation assay, all 15 P. infestans isolates collected from China, Europe and South America could be positively detected, but results of the other 9 Phytophthora species infecting different plants, fungal and bacterial plant pathogens tested were negative. The detection limit of this assay is 1 pg P. infestans DNA. Moreover, the LAMP-PiSMC assay is able to detect P. infestans from infected leaves, tubers and soil. Taken together, this study reports the development of a specific and sensitive LAMP-PiSMC assay for early diagnosis of potato late blight.